Green-synthesized cyclophosphamide-loaded magnetite nanocomposites for in vitro anti-cancer activity against U-87 glioblastoma cells - Ayesha Bibi; Ayesha Azmat; Salman Zafar (Results in Chemistry, 2025)
Glioblastoma multiforme is one of the most aggressive and treatment-resistant brain tumors, necessitating the development of novel drug delivery systems to enhance therapeutic efficacy. This study focuses on the green synthesis, characterization, and anti-cancer potential of cyclophosphamide-loaded magnetite nanoparticles for targeted glioblastoma therapy. Magnetite nanoparticles were synthesized, using Vitis vinifera (raisin) extract via a green precipitation method, and subsequently loaded with cyclophosphamide. The resulting nanocomposite was characterized using advanced spectroscopic and microscopic techniques. Drug loading, encapsulation efficiency, and release kinetics were evaluated, under physiological (pH 7.4) and acidic (pH 5.5) conditions. The genotoxic effects were assessed using the comet assay, while anti-cancer efficacy, against U-87 glioblastoma cells, was determined via the crystal violet assay. The nanocomposite exhibited a 15.8% drug loading capacity and an encapsulation efficiency of 79.4%, with a controlled biphasic drug release pattern, demonstrating enhanced release in acidic conditions (87.4% at pH 5.5 vs. 61.8% at pH 7.4). The negative surface charge (−13.05 mV) confirmed its stability and biocompatibility. Genotoxicity studies indicated dose-dependent DNA damage, validating its mechanism of action. The drug-loaded nanocomposite showed a significantly lower IC₅₀ (422 μM) as compared to the free drug (5272 μM), demonstrating enhanced cytotoxicity against U-87 cells. The nanocomposite thus, exhibits improved bioavailability, controlled drug release, and enhanced anti-cancer efficacy, making it a promising candidate for glioblastoma therapy. Further in vivo studies are warranted to evaluate its clinical potential.